Left Amyand’s Hernia in A 1-Year-Old Male Infant: Report of a Rare Case in Common Presentation - Fikri E.; Alnaz A. (Acta Medica Bulgarica)
Amyand’s hernia is a rare type of hernia with the appendix and cecum trapped in a hernial sac. A one-year-old male infant was referred with irreducible left inguinal hernia for about 1 week. No signs of intestinal obstruction were presented, and pain was tolerated. A herniotomy was performed on the patient. Intraoperatively, the appendix and cecum were found in the left hernial sac, which this rare presentation named left Amyand’s hernia. Cecum and appendix were considered normal. No perforation and significant inflammation were found; hence, no appendectomy was performed. Left Amyand’s hernia is a very rare case, mostly in pediatric surgery, in which the current decision of diagnosis-making can only be made intraoperatively.